Unravelling the influence of management support, colleague support, compensation and benefits, and job security on employee job performance during the business recovery phase / Nur Yasmin Muhamad Raffin ... [et al.] - Muhamad Raffin, Nur Yasmin; Borhnnudin, Rosnidar; Zailani, Noor Zalina; Ramli, Suriana (2023)
A heightened emphasis on business recovery and expansion characterizes the post-pandemic era. According to reports, numerous organizations in Malaysia have encountered a decline in their business performance due to the ongoing pandemic. The restoration of the company's performance is significantly dependent on its human resources. The performance of employees is a critical factor that determines the success or failure of an organization. Given the unfavourable circumstances, it is imperative to recognize the issues that may impact employee performance during crisis recovery. Therefore, individuals who exhibit a high level of commitment towards an organization are more inclined to exert more significant effort and dedication compared to their less devoted counterparts. Hence, this research investigates the correlation between the independent variables, specifically management support, remuneration and benefits, colleague support, and job security, and the dependent variable of employee work performance. This research employs Herzberg's Two-Factor Theory to elucidate the correlation between the independent and dependent variables. The present study employs a quantitative methodology, utilizing an online questionnaire as the significant data collection instrument. 86 responses were analyzed using the Statistical Package for Social Science (SPSS) version 27. The study results indicate a favourable and statistically significant correlation between colleague support, job security, and employee work performance. There is no significant association between managerial support, compensation, and benefits and employee work performance. The primary determinant in this study is the level of assistance colleagues provide. The factors of colleague support and job security are indicative of hygiene considerations, which serve to mitigate employee unhappiness. Hence, the findings of this research can serve as a valuable framework for organizations to improve their managerial practices, particularly concerning fostering colleague support and ensuring job security to raise satisfaction with work and subsequently boost employee job performance.